2014
DOI: 10.1586/14779072.2014.977258
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerotic renal artery stenosis and revascularization

Abstract: Atherosclerotic renovascular disease is the most common cause of secondary hypertension. The patients with renovascular disease are at increased risk for adverse cardiac outcomes. Recent trials comparing medical therapy alone to medical therapy with stenting are flawed, but lay to rest any existing debate that unselected revascularization is unwarranted; however, revascularization may be appropriate in high-risk populations. Defining an appropriate population for revascularization is an area of ongoing study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 65 publications
0
7
0
1
Order By: Relevance
“…Such conclusions may help to decrease the risks of an unnecessary exposure of patients with RVD to the potential risks of this intervention, although renal angioplasty and stenting may still be beneficial in selected patients with RVD 4 . Furthermore, a puzzling fact is that regardless of the chosen therapeutic strategy (medical or interventional), meaningful recovery of renal function is observed in a relatively small fraction of the patients 1, 2 . Therefore, if the vascular obstruction is not the main problem, targeting the renal parenchyma could likely be a major determinant on outcomes and recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such conclusions may help to decrease the risks of an unnecessary exposure of patients with RVD to the potential risks of this intervention, although renal angioplasty and stenting may still be beneficial in selected patients with RVD 4 . Furthermore, a puzzling fact is that regardless of the chosen therapeutic strategy (medical or interventional), meaningful recovery of renal function is observed in a relatively small fraction of the patients 1, 2 . Therefore, if the vascular obstruction is not the main problem, targeting the renal parenchyma could likely be a major determinant on outcomes and recovery.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of renovascular disease (RVD) are still poor, and there is a noticeable lack of consensus regarding the best therapeutic strategy for these patients, which adds a burden of uncertainty to the treatment selection and course. Regardless of the chosen therapy (medical, interventional, or combined therapy), patients with RVD improve in about 30% of the cases 1, 2 . Furthermore, the results of the CORAL study support the notion that pharmacological or interventional (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies and larger controlled trials have shown that up to 50% of patients may have some benefit from RAS treatment with PTRA (12). As these results showed, selection of the appropriate subgroup is key when considering patients for PTRA and unselected PTRA based on the pure detection of RAS is not recommended (4,5,15). It has been suggested that those patients with a decreased renal function may benefit from RAS treatment with PTRA (16).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of percutaneous transluminal renal angioplasty and stenting (PTRA) for hemodynamic relevant RAS on renal function as well as the prediction of patients in whom PTRA improves renal function is a matter of debate (1,4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Studier på endovaskulaer invensjon har vist bedring (definert som bedring i blodtrykk med/uten medisiner) hos 56 -82 % av pasientene (14 -17). Gode effekter av stenter i nyrearterier er påvist i utvalgte voksenpopulasjoner (18). Hos barn, derimot, bør stent bare brukes i spesielle tilfeller (19).…”
Section: Diskusjonunclassified